Transformative Metaverse Pedagogy for Intangible Heritage: A Gamified Platform for Learning Lanna Dance in Immersive Cultural Education - Kannikar Intawong; Perasuk Worragin; Songpon Khanchai; Kitti Puritat (Education Sciences, 2025)
This study explores the design of Metaverse technologies for preserving and teaching Lanna Dance, a traditional cultural heritage of Northern Thailand. It addresses the challenges of sustaining intangible cultural heritage by developing an immersive learning system that integrates motion capture, generative AI, and gamified virtual environments. Grounded in Situated Learning Theory and adaptive learning, the platform features four interactive zones, the Motion Showcase, Knowledge Exhibition, Video and AI Interaction, and Interactive Game Zone, offering learners multifaceted, context-rich experiences. Using a quasi-experimental design with 36 participants, the study evaluates learning outcomes, motivation, and user satisfaction. Results show significant improvements in knowledge acquisition and intrinsic motivation, along with high usability scores, indicating the effectiveness of immersive digital environments in enhancing cultural appreciation and skill development. The findings offer practical insights into Metaverse design for immersive cultural education, supporting educators, cultural institutions, and policymakers in developing scalable and engaging solutions for preserving intangible heritage through emerging technologies.